Longitudinal association between motor and obsessive compulsive symptoms in patients with psychosis and their unaffected siblings - Swets, Marije (Eur Arch Psychiatry Clin Neurosci, 2018)
Little is known about the co-prevalence of obsessive compulsive symptoms (OCS) and motor symptoms in patients with psychotic disorders. Cross-sectional associations between OCS and motor symptoms were assessed at baseline and at 3 years follow-up in patients (n = 726) with psychotic disorders and in their unaffected siblings (n = 761) from the Dutch Genetic Risk and Outcome of Psychosis (GROUP) study. Furthermore, longitudinal associations between changes in OCS and motor symptoms were evaluated. At baseline, OCS was not associated with any motor symptom (akathisia, dyskinesia, parkinsonism or dystonia) in patients. At follow-up, patients with OCS reported significantly more akathisia. Dividing the patients into four groups—no OCS, OCS remission with OCS only at baseline, OCS de novo with OCS only at follow-up and a persistent OCS group—revealed that the OCS de novo group already reported more akathisia at baseline compared to the no-OCS group. At follow-up, both the OCS de novo and the persistent OCS group reported more akathisia. These results remained significant after correcting for relevant confounders clozapine, GAF score, PANSS-negative score and IQ. Motor symptoms at baseline were significantly associated with OCS at follow-up, but not the other way around. In siblings, OCS at baseline was associated with akathisia, but this association was lost at follow-up. Results suggest that motor symptoms might precede co-occurring OCS in patients with psychotic disorders. However, no inference can be made about causality, and further prospective research is needed to investigate this assumption.